KEANEKARAGAMAN JENIS SERANGGA PADA LAHAN TANAMAN CABAI YANG BERBATASAN DENGAN HUTAN - Firmansyah, Firmasnyah; Karyaningsih, Ika; Nurlaila, Ai (Wana Raksa, 2023)
Karangsari Village, Darma district, Kuningan Regency is one area that has agricultural land which is mostly planted with vegetable crops, the presence of pollinating insects on agricultural land in Karangsari Village is very important in helping the pollination process, resulting in the production of vegetable crops. Karangsari Village is a forest edge area in Kuningan Regency which is rich in flora and fauna that have not been identified. The problems studied in this study are 1) How is the diversity of insect species on the chili plant field 2) What is the ecological function of the insects found on the chili plant field. The method used in this research is the survey method and scan sampling. Based on observations made for 7 days, there were 7 orders, 21 families, and 26 species with ecological roles such as pests, predators, parasites, decomposers, natural enemies, and pollinators while the Shannon-Wiener index value was 2.05.Desa Karangsari Kecamatan Darma Kabupaten Kuningan merupakan salah satu daerah yang mempunyai lahan pertanian yang banyak ditanami tanaman sayuran, keberadaan serangga penyerbuk pada lahan pertanian di Desa Karangsari sangat penting dalam membantu proses penyerbukan sehingga menghasilkan produksi tanaman sayuran. . Desa Karangsari merupakan kawasan tepi hutan di Kabupaten Kuningan yang kaya akan flora dan fauna yang belum teridentifikasi. Permasalahan yang dikaji dalam penelitian ini adalah 1) Bagaimana keanekaragaman jenis serangga pada lahan tanaman cabai 2) Bagaimana fungsi ekologis serangga yang terdapat pada lahan tanaman cabai. Metode yang digunakan dalam penelitian ini adalah metode survei dan scan sampling. Berdasarkan pengamatan yang dilakukan selama 7 hari, terdapat 7 ordo, 21 famili, dan 26 spesies dengan peran ekologis seperti hama, predator, parasit, pengurai, musuh alami, dan penyerbuk sedangkan nilai indeks Shannon-Wiener sebesar 2,05.